CONCEPT OF SWITCHING MODE OF REPRODUCTION AND EVOLUTIONARY THEORY: ISSUES OF METHODOLOGY - V. I. Mayevsky (Вестник университета)
The purpose of the article is to show that the innovation development of the economy, being the subject of research of evolutionary economic theory, occurs mainly in the switching mode, and therefore is organically linked with the so-called switching mode of reproduction, which is currently being intensively developed at the Institute of Economics of the Russian Academy of Sciences. For representatives of the Orthodox Economic Science, all subjects are homogeneous, that is, they are characterized by rational behavior, the intention to maximize profits and the striving for equilibrium states. Evolutionary economists consider this homogeneity to be far from obvious. They pay primary attention to innovative development as a process of qualitative changes, distinguish subjects who implement qualitative changes and subjects who do not, but rather counteract changes. The concept of a switching mode of reproduction is based on a fundamentally different methodological prerequisite and therefore is a development of both evolutionary and orthodox economic theory.